Digital society: sociological education in the «electronic» world of the 21st century - Danilov, Alexander N.; Rubanov, Anatoly V.; Korshunov, Gennady P.; Tereshchenko, Olga V.; Efimova, Nadezhda V.; Sarna, Alexander Ya.; Tereshchenko, Maria S.; Belousova, Anastasia E.; Podolyak, Egor E.; Sidorenko, Anastasia P. (Journal of the Belarusian State University. Sociology, 2019)
The round table is devoted to a discussion of the problems associated with the digitalization of modern society. The discussing questions cover a wide range of problems: the origins of the information society, its development trends, new information and communication technologies in higher education and in scientific activity, the possibility of sociological research, social networks, media, the use of Internet resources in sociological research. According to the participants, the digital wave has been launched, governments are creating digitalization programs: the Digital Economy Act, adopted by the British Parliament, has been in force since 2010, a strategy and concrete plans have been developed; USA, Singapore, Germany are already really living in a digital economy. The current digitalization boom has arisen after the world started talking about a new industrial revolution of the 21st century. The initiator was the American economist Jeremy Rifkin, who in 2011 published the book «The Third Industrial Revolution». He showed appeared technologies changing life, production and the essence of management in general. The Fourth Industrial Revolution is based on the specific Industry 4.0 project, which was prepared in Germany. It shows how to realize new opportunities in the economy, increase labor productivity, and make a breakthrough in the quality of human life in modern conditions. A new digital project Society 5.0 has been prepared in Japan. In the Republic of Belarus, the attention is paid to digitalization issues, documents governing its development have been adopted at the state level, Belarus is initiating the development of this process at the international level. In addition, the authors pay attention to the possible negative consequences of digitalization and urge not to leave this side unattended.